Neurocutaneous flaps for soft tissue reconstruction of the knee, lower leg, ankle and foot: clinical experience with 32 patients - Jovanović, Mladen; Janjić, Zlata; Komarčević, Aleksandar; Mijatović-Jovanović, Vesna; Marinković, Marija; Tomić, Miroslav (Vojnosanitetski pregled, 2021)
Background/Aim. Neurocutaneous flaps (NF) are the type of fasciocutaneous flaps whose clinical application has increasingly grown over the years. They have become an indispensable step in the reconstructive ladder for the small and medium soft tissue defects of the lower leg and foot. The aim of this study was to analyse the results of the treatment of patients with lower extremity soft tissue defects caused by trauma, infection, tumour removal or unstable scar formation, which were reconstructed with a variety of NF. Methods. This retrospective study includes 32 consecutive patients with soft tissue defects of the lower limb, treated in the Clinical Centre of Vojvodina from January 2004 to April 2017. All the operations were performed in regional anaesthesia with pneumatic tourniquet. Design of the flap and length of the pedicle were determined by the size and position of the recipient site after necessary debridement. The flap was harvested, rotated and positioned in the defect region. The patients and flap data were summarized upon their collection. Results. The average age of the patients, mostly males (81.2%), was 46.7 years. Distally based sural flaps were used in a majority of patients (56.2%), followed by the distally based saphenous (21.9%), lateral sural (12.5%) and proximally based sural flaps (9.4%). Defects were most often localized on the distal third of the lower leg and on the ankle (53.1%). The most common indication for surgery were trauma (46.9%) and chronic infection (31.2%). A satisfactory coverage of the defect was achieved in all 32 patients with no flap loss. A partial necrosis of the flap due to prolonged venous congestion was noted in 3 (9.4%) patients, which were healed by second intention or with delayed skin grafting. Five (15.6%) patients developed a localised infection. The infection signs withdrew spontaneously in 2 cases and after a surgical revision in 3 cases, where osteitis of the tibia had persisted. One of them required the Ilizarov orthopaedic procedure after bone resection. Conclusion. NF proved to be a paramount alternative to free-flap reconstruction of the lower limb. Intensive clinical application can be explained by the fact that it is a less technically demanding and time consuming surgical procedure with no major source vessel sacrifice. The reliability and safety of their utilisation are confirmed by our clinical data.
Keywords: ankle, joint; foot; lower extremity; reconstructive surgical procedures; surgical flaps; treatment outcome.